“You could get the best of both breeds or the worst of both”: UK public attitudes towards crossbreeding in dogs - with a specific focus on brachycephalic dogs - Elizabeth Youens; Dan G. O’Neill; Zoe Belshaw; Johanna Neufuss; Mickey S. Tivers; Rowena M. A. Packer (PLoS ONE, 2026)
Extreme conformation and reduced genetic diversity are recognised to lead to severely reduced health, welfare and longevity in certain dog breeds. There is growing interest in applying strategic crossbreeding to promote more moderate conformations and greater genetic diversity within currently problematic breeds. Crossbreeding could therefore lead to more rapid and effective improvements in welfare compared to current practices of within-breed selection. Deliberate crossbreeding between distinct different dog breeds is not a new concept; it was historically commonly used to create the current pure breeds, to increase genetic diversity and to bring new physical and/or temperament traits into existing breeds. However, a recent surge in the popularity of ‘designer crossbreeds’ (intentional crosses between established purebreds) has elicited fresh interest around the potential positives and negatives of crossbreeding practices. Further research on crossbred brachycephalic dogs is urgently required for a greater understanding of the motivators and barriers to their acquisition. An online survey explored factors that motivate dog breed choice and acquisition of both crossbreed and purebred dogs. In addition, the survey used both closed and open questioning to explore the UK public’s perceptions of crossbreeding, specifically (i) between a brachycephalic breed and a non-brachycephalic breed, and (ii) between two non-brachycephalic breeds. Free-text results were analysed using content analysis and subsequently quantified. Results from 4,899 participants identified that key motivators to acquire a brachycephalic crossbreed vs a brachycephalic purebred included perceptions of improved health, including the reduction in risk of breed and conformation-related disorders, and increased genetic diversity. However, the desire to acquire a purebred dog, or even a specific breed, remained a significant barrier to crossbreed acquisition, alongside concerns surrounding the ethics of crossbreeding. Other barriers included perceived negative changes to appearance and temperament of the offspring from crossbreeding. The current study identified a common set of acquisition decision-making factors across all ownership groups, including desiring a dog who the owner perceives to enjoy being loved and to enjoy physical affection, but further demonstrated that good health is of motivational low priority to some dog owners, particularly to owners of purebred brachycephalic dogs. The mix of positive and negative public perceptions and beliefs around crossbreeding and crossbreed dogs demonstrate the need for further research into the health, temperament and appearance of brachycephalic crossbreed dogs. The suitability of crossbreed dogs as an alternative to certain current purebred breeds with high risk of genetic or conformational disorders depends on both public desire and on evidence-based selection of suitable breeds to encourage crosses which maximise canine welfare.